A Method for Fast Au-Sn Bonding at Low Temperature Using Thermal Gradient - Wenchao Wang; Ziyu Liu; Delong Qiu; Zhiyuan Zhu; Na Yan; Shijin Ding; David Wei Zhang (Micromachines, 2023)
Flip chip bonding technology on gold–tin (Au-Sn) microbumps for MEMS (Micro Electro Mechanical Systems) and 3D packaging is becoming increasingly important in the electronics industry. The main advantages of Au-Sn microbumps are a low electrical resistance, high electrical reliability, and fine pitch. However, the bonding temperature is relatively high, and the forming mechanism of an intermetallic compound (IMC) is complicated. In this study, Au-Sn solid-state diffusion (SSD) bonding is performed using the thermal gradient bonding (TGB) method, which lowers bonding temperature and gains high bonding strength in a short time. Firstly, Au-Sn microbumps with a low roughness are prepared by using an optimized process. Then, Au-Sn bonding parameters including bonding temperature, bonding time, and bonding pressure are optimized to obtain a higher bonding quality. The shear strength of 23.898 MPa is obtained when bonding in the HCOOH environment for 10 min at the gradient temperature of 150 °C/250 °C with a bonding pressure of more than 10 MPa. The IMC of Au-Sn is found to be Au-Sn and Au5Sn. The effect of annealing time on the IMC is also investigated. More and more Au5Sn is generated with an increase in annealing time, and Au5Sn is formed after Sn is depleted. Finally, the effect of annealing time on the IMC is verified by using finite element simulation, and the bonding strength of IMC was found to be higher when the bonding temperature is 150 °C at the cold side and 250 °C at the hot side. The temperature in the bonding area can reach 200 °C, which proves that the Au-Sn bonding process is solid-state diffusion because the temperature gradient reaches 2500 °C/cm.